Plant functional traits related to aboveground tree biomass in cloud forests of southeastern Mexico - Noé Velázquez-Rosas; Elizabeth Fuentes Romero; Betsabé Ruiz-Guerra; Hugo López Rosas; Norma Eugenia García Calderón (Trees, Forests and People)
Cloud forests are one of the most important ecosystems on a global scale, due to their biodiversity and the services they provide to human populations. Understanding the causal factors determining the structural variation and functioning of cloud forests continues to be one of the most relevant research challenges in these forests. In this study, we analyzed the relationship of functional responses (foliar and wood density) with aboveground tree biomass in cloud forest communities, with the purpose of identifying the causal factors determining the structural variation of these communities along an altitudinal gradient. Tree biomass varied between 124.02 and 487.93 Mg ha-1; however, it did not exhibit a gradual change associated with altitude. Foliar N content, C:N ratio, and wood density were associated with tree biomass production, suggesting that N nutrient stress may explain the inconsistent patterns of biomass production. The spatial variation of nutrient stress in these communities may be caused by topographic variation, which determines differential nutrient leaching processes, as well as the composition of plant communities and foliar nutritional quality.